(untitled) (Journal Of Educational and Psychological Researches, 2023)
The current research aims to identify the achievement of goals and the significance of the differences in achieving goals according to the variable of gender (male-female), specialization (scientific-human), and the stage (Master-PhD) for postgraduate students. To achieve the goals of the current research, the researcher developed a scale of achieving goals that was built according to the theory of (Lock & Latham 1990), which was applied to a sample of (257) male and female students who were selected randomly with a proportional distribution for the academic year (2021-2022). The scale of achieving goals consists of (30) items. The current research found that the research sample of postgraduate students has achieved their goals in general, but according to the gender variable (male-female) and the stage (Master-PhD), there are no differences between them. As for the specialization, it was found that there are differences between them in favor of students of scientific specialization. ‏In light of these results, the researcher presented some recommendations and suggestions, as shown in the fourth chapter.